Process-Structure-Property Interdependencies in Non-Isothermal Powder Bed Fusion of Polyamide 12 - Schlicht, Samuel; Cholewa, Simon; Drummer, Dietmar (Journal of Manufacturing and Materials Processing, 2023)
Non-isothermal laser-based powder bed fusion (LPBF) of polymers suggests the potential for significantly extending the range of materials applicable for powder-based additive manufacturing of polymers, relying on the absence of a material-specific processing window. To allow for the support-free manufacturing of polymers at a build chamber temperature of 25 °C, applied processing strategies comprise the combination of fractal exposure strategies and locally quasi-simultaneous exposure of distinct segments of a particular cross section for minimizing crystallization-induced part deflection. Based on the parameter-dependent control of emerging cooling rates, formed part morphologies and resulting mechanical properties can be modified. Thermographic in situ measurements allow for correlating thermal processing conditions and crystallization kinetics with component-specific mechanical, morphological, and microstructural properties, assessed ex situ. Part morphologies formed at crystallization temperatures below 70 °C, induced by reduced laser exposure times, are characterized by a nano-spherulitic structure, exhibiting an enhanced elongation at break. An ambient temperature of 25 °C is associated with the predominant formation of a combined (α + γ)-phase, induced by the rapid cooling and subsequent laser-induced tempering of distinct layers, yielding a periodic microstructural evolution. The presented results demonstrate a novel approach for obtaining nano-spherulitic morphologies, enabling the exposure-based targeted adaption of morphological properties. Furthermore, the thermographic inline assessment of crystallization kinetics allows for the enhanced understanding of process-morphology interdependencies in laser-based manufacturing processes of semi-crystalline polymers. <
Keywords: non-isothermal; powder bed fusion; laser sintering; low temperature powder bed fusion; polyamide 12